Manajemen Peningkatan Mutu Pendidikan - Fadhli, Muhammad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2017)
The low quality of education in Indonesia is actually a long-standing discussion. But until now permasalahn the quality of education is also finished. Quality education is the expectations and demands of all stakeholders in education. Everyone will certainly prefer menntut science at an institution that has a good quality. On this basis, schools / educational institutions should be able to provide good service and quality in order not to be abandoned and unable to compete with other educational institutions. From a variety of views, criteria and indicators that we can take that quality education could be improved if the school has one) support from the government, 2) Leadership Principals effective, 3) Performance good teacher, 4) relevant curriculum 5) graduates quality, 6) culture and climate of effective organization, 7) the support of the community and parents. Implementation of management in improving the quality of education is a real solution is to be hope in order to manage the indicators of the quality of education to create a synergy in efforts to improve the quality of education. Abstrak Rendahnya mutu pendidikan di Indonesia sebenarnya merupakan diskusi yang telah lama ada. Namun hingga saat ini permasalahn mutu pendidikan tidak juga kunjung selesai. Pendidikan yang berkualitas merupakan harapan dan tuntutan seluruh stakeholder pendidikan. Semua orang tentunya akan lebih suka menntut ilmu pada lembaga yang memiliki mutu yang baik. Atas dasar ini maka sekolah/ lembaga pendidikan harus dapat memberikan pelayanan dan mutu yang baik agar tidak ditinggalkan dan mampu bersaing dengan lembaga pendidikan lainnya. Dari berbagai pandangan, kriteria serta indikator yang dapat kita ambil bahwa pendidikan yang bermutu dapat ditingkatkan apabila sekolah memiliki 1) dukungan dari pemerintah, 2) Kepemimpinan Kepala sekolah yang efektif, 3) Kinerja guru yang baik, 4) kurikulum yang relevan, 5) lulusan yang berkualitas, 6) budaya dan iklim organisasi yang efektif, 7) dukungan masyarkat dan orang tua siswa. Implementasi manajemen dalam peningkatan mutu pendidikan merupakan sebuah solusi nyata yang menjadi harapan agar dapat mengelola indikator mutu pendidikan untuk saling bersinergi dalam upaya peningkatan mutu pendidikan Kata Kunci: Peningkatan Mutu, Manajemen Mutu Pendidikan